Association of serum thyroid hormone levels with positron emission tomography imaging in non‐demented older adults. Issue 3 (15th March 2022) - Goto, Megumi; Kimura, Noriyuki; Matsubara, Etsuro
Background: Background: Although increasing evidence indicates that even variations in normal range thyroid function are associated with Alzheimer's disease (AD), the association between serum thyroid hormone levels within the reference range and AD biomarkers remains unclear. This study examined whether variations in thyroid hormones within the reference range are associated with brain amyloid burden and cortical glucose metabolism in older adults without dementia. Methods: One hundred and two non‐demented older adults underwent 11 C‐Pittsburgh Compound B positron emission tomography (PiB‐PET), 18 F‐fluorodeoxyglucose (FDG)‐PET, and measurement of serum thyroid‐stimulating hormone (TSH), free triiodothyronine (T3), and free thyroxine (T4) levels. The discrimination between PiB‐negative and PiB‐positive subgroup was made on the basis of a subject's cortical uptake value ratio greater than 1.4. The association of serum thyroid hormone levels with global PiB or FDG uptake, and PiB or FDG uptake in each region of interest, including frontal and temporoparietal lobes and posterior cingulate gyrus, was analysed using a multiple regression model with adjustment for covariates, including age, gender, years of education, apolipoprotein E4 status or PiB uptake value. Results: In the PiB‐positive subgroup, the serum TSH levels positively associated with the global FDG uptake (β = 0.471, P  = 0.003) and FDG uptake in the frontal and temporoparietal lobes (β = 0.466, P  = 0.003, β = 0.394, P  = 0.012, respectively); the serum‐free T3 levels negatively associated with the FDG uptake in the temporoparietal lobe and posterior cingulate region (β = −0.351, P  = 0.033, β = −0.544, P  = 0.002, respectively). The PiB‐negative subgroup showed no significant associations. The serum thyroid hormone levels did not correlate with the global PiB uptake and PiB uptake in each region. Conclusions: The variations in the thyroid hormones within the reference ranges are associated with glucose metabolism, particularly in the specific regions affected by the neuropathologic changes of AD, in non‐demented older adults with brain amyloid burden.